What is the effect and mechanism of kinesiology tape on muscle activity?. Issue 2 (April 2018) - Bagheri, Rasool; Pourahmadi, Mohammad Reza; Sarmadi, Ali Reza; Takamjani, Ismail Ebrahimi; Torkaman, Giti; Fazeli, Sayyed Hamed
Abstract: Objective: This study aimed to evaluate the effects of kinesiology tape, anesthesia, and kinesiology tape along with anesthesia, on motor neuron excitability. Participants: Participants included 20 healthy men aged 20–35 years, who were examined over 5 sessions. Intervention: The five experimental sessions included: control without applying the kinesiology tape or Eutectic Mixture of Local Anesthetics (EMLA); treatment only with EMLA; only kinesiology tape application; only sham tape application; and treatment with kinesiology tape and EMLA. Main outcome measures: The H-reflex recruitment curve of the soleus and lateral gastrocnemius was recorded by a blinded assessor in the 5 separate sessions randomly assigned with 48 h washout periods. The major H-reflex parameters include: the Hmax /Mmax ratio, the H-reflex threshold stimulation intensity (Hth ), the intensity of maximum H-reflex (IntensityHmax ), the H-reflex ascending slope (Hslp ), and the H-reflex ascending slope fixed into the first three points (first Hslp ). Results: The H-reflex parameters (H slope, first Hslp, Hth, and IntensityHmax ) were facilitated by application of the kinesiology tape with and without EMLA; however, EMLA inhibited the H-reflex parameters (Hmax /Mmax ratio, Hslp, first Hslp, and Hth ) in both the soleus and lateral gastrocnemius. The sham tape did not alter the H-reflex recruitment curve parameters. The statistical model revealed a significant difference between the kinesiology tape and the sham tape and control sessions, between kinesiology tape–EMLA and EMLA, and between kinesiology tape–EMLA and control session. Conclusions: Results suggest that the kinesiology tape facilitates the muscle activity and the underlying mechanism on the gastrosoleus motor neuron pool involves the cutaneous receptors.